Zooplankton Composition of Pulumur Stream (Tunceli-Turkey) - Saler, Serap; Haykir, Hilal (Medwell Online, 2011)
This study was completed with periodical surveys in Pulumur-stream between November 2009-October 2010 period. During the study, a total of 21 species (15 belonged to genus of Rotifera, 4 to Copepoda and 2 Cladocera) were found in Pulumur stream. All of the zooplanktonic species have been detected for the first time in Pulumur-stream. Also some water parameters (pH, dissolved oxygen, electrical conductivity and water temperature) were measured during field trips.
Keywords: Zooplankton; rotifera; cladocera; copepoda; Pulumur stream; Turkey